Educating for virtue: How wisdom coordinates informal, non-formal and formal education in motivation to virtue in Canada and South Korea. Issue 1 (2nd January 2019) - Ferrari, Michel; Bang, Hyeyoung; Ardelt, Monika; Feng, Zhe
ABSTRACT: How do different forms of education contribute to value preferences? Clearly, informal education through personal experiences that shape one's sense of identity and frame cultural expectations and opportunities (as indexed by culture, gender and age-cohort), non-formal education through religious traditions and formal state-mandated education all contribute to value preferences in culturally-specific ways. However, wisdom should allow people to coordinate culturally-specific education in ways that promote prosocial values. Our study considered the relative strength of four value-orientations from Schwartz's Personal Values Questionnaire and of 15 core virtues among 189 participants from Canada and South Korea; half were older and half younger adults. 101 were emerging adults (aged 18–25) and 88 were retired older adults (aged 60–80). Multivariate regression analyses show that, although all three forms of education influenced value orientation in culture-specific ways in both Canada and South Korea, formal education was critical to cultivating the wisdom needed to coordinate and adjudicate between different values so as to live well.